2020
DOI: 10.3906/vet-2003-28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and slaughter age on growth, slaughter, and carcass characteristics in Lindovskaya geese reared under breeder conditions

Abstract: The study was conducted to determine growth, slaughter, and carcass characteristics of Lindovskaya geese. While a total of 237 goslings, 101 males, and 136 females were used to determine their growth characteristics, 16 male geese in total were used for the detection of the slaughter and carcass characteristics. Each slaughter group (12 weeks and 16 weeks old) consisted of 8 male geese. It was determined that the effect of sex on body weight values by week was significant (P < 0.05). In addition to this, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
4
2
2
Order By: Relevance
“…Research on the influence of the sex of Czech Goose and Eskildsen Schwer on slaughter traits also confirmed the differences, including the slaughter weight ( Uhlírová et al, 2018 ). In the case of Lindovskaya geese, similar results were shown between sex ( Akbaş et al, 2020 ).…”
Section: Introductionsupporting
confidence: 70%
“…Research on the influence of the sex of Czech Goose and Eskildsen Schwer on slaughter traits also confirmed the differences, including the slaughter weight ( Uhlírová et al, 2018 ). In the case of Lindovskaya geese, similar results were shown between sex ( Akbaş et al, 2020 ).…”
Section: Introductionsupporting
confidence: 70%
“…Recent research has found significant differences in muscle and carcass fat content between male and female geese ( Lisiak et al, 2021 ). Such differences, including slaughter weight, were also confirmed in a study on the effect of sex on slaughter characteristics of heavy Czech and Eskildsen Schwer hybrid geese ( Uhlirova et al, 2018 ), and similar results were observed in male and female Lindowskaya geese ( Akbaş et al, 2020 ).…”
Section: Introductionsupporting
confidence: 68%
“…The overall mean of feather weight determined as 294.62 g in Gray Hungarian geese and 215.06 g in German Mast geese werelower than those of native breeds reported by Tilki and İnal (2004), similar to those of reported by Boz (2019), and higher than those of reported by Kırmızıbayrak and Önk (2011). The mean blood weight in Gray Hungarian and German Mast geese was lower than the values in the study of Akbaş et al (2020), Önk (2011), andBoz (2019), and similar to the values reported by , Saatcı et al (2009), and Kırmızıbayrak and Kuru (2018). It is suggested that these differences may be due to possible differences in genotype, age, or duration of bleeding.…”
Section: Discussioncontrasting
confidence: 39%
“…Hot carcass dressing percentagevalues were 66.27% and 67.99% in Gray Hungarian and German Mast geese, respectively. In literature, carcass dressing percentage in geese generally varies between 60-73% and increases with age Kırmızıbayrak and Önk 2011;Akbaş et al 2020;Boz and Sarıca 2021). The carcass yield of approximately 67-68% obtained in the present study is considered to be at an acceptable level considering the nutritional conditions and age.…”
Section: Resultsmentioning
confidence: 52%